Etnografi Dakwah dalam Tradisi Berkaul Adat pada Masyarakat Minangkabau - Fauzi, Ahmad; Fatoni, Uwes; Sutisna, Dede (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research aims to understand the processions, activities and messages of da’wah in traditional vows in Nagari Lalan, Minangkabau. This activity was analyzed using sociocultural theory, which links culture with Islamic preaching. Through qualitative ethnographic methods, researchesr directly observe the interaction of da’wah and traditional traditions in society. The result show three main aspects: the traditional vow procession, which includes deliberation, mutual cooperation, and slaughtering rites and bajamba; da’wah activities in the form of deliberation and almsgiving, as well as da’wah bil hal and bil verbaly; and the message of da’wah, both physical and spiritual conveyed in this activity